INFLUENCE OF PREFABRICATED FOAM CONCRETE AS INFILL WALL ON THE STRENGTH DUE TO CYCLIC LOADING - Amiruddin, A. Arwin; Parung, Herman; Tjaronge, M. W.; Rita Irmawaty; Mansyur; Tumpu, M. (GEOMATE Journal, 2022)
Many areas of Indonesia are located near earthquake faults, resulting in the recurrence of earthquake phenomena in various regions of Indonesia. This research is an experimental study on the behavior of prefabricated foam concrete as wall infill material under lateral cyclic loading. This study analyzed the relationship between load and displacement in prefabricated foam concrete as an infill wall. The test object consisted of 2 wall models: reinforced concrete frames (DB 1) and prefabricated foam concrete infill wall (DB 2). Lateral cyclic loading with displacement control method is carried out to evaluate the structural behavior of the wall regarding ASTM E2126-02a. The test results showed that the strength value of the DB 2 specimen resulted in a 29.61% increase of strength than the DB 1 specimen. Furthermore, the relative stiffness degradation on both specimens is not too significant in both the loaded and unloaded state, so there may be no pinching effect. It’s more likely to lead to a more stable condition with higher energy dissipation capability without decreasing the strength of the specimen when compared to the DB 1 specimen. Therefore, foam concrete precast panel can be utilized as an alternative infill material for walls on a reinforced concrete frame structure to be replaced with clay bricks, hebel, batako, etc